The Impact of Artificial Intelligence Development on Occupational Health and Safety – A Panorama of the Phenomenon - Florczak, Izabela; Stefański, Krzysztof (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
This article presents a broad picture of the impact of artificial intelligence on occupational health and safety, taking into account both the opportunities and challenges associated with this process. On the one hand, artificial intelligence has great potential for automating processes related to monitoring and controlling occupational risks and improving working conditions. At the same time, there are numerous risks associated with the use of this technology in the work environment. The article also addresses the issue of ethics and privacy in the context of the use of AI in the work environment, as well as risk management, pointing to the need for appropriate regulation.